Agency in Sales: A Comparative Jurisprudential Study with Positive Laws - Dr. Osama Ghayth Faraj Al-Daiki (Journal of Scientific and Human Dimensions, 2026)
This research paper addresses the topic of "Tawliya" (sale of trust) as a type of trust-based sale in Islamic jurisprudence. It involves selling at cost price without profit or loss. The study aims to clarify its nature, ruling, and conditions, while also reviewing points of disagreement among the four schools of Islamic jurisprudence and highlighting its contemporary applications, comparing it with positive law. The paper affirms that Tawliya is permissible according to Islamic law, based on the consensus of scholars, provided that the initial cost price is disclosed and the contract is free from uncertainty and usury. It discusses points of disagreement, such as the requirement of knowing the initial price, the ruling on selling before taking possession of the goods, expenses related to the initial cost, the ruling on Tawliya for non-fungible goods, and the consequences of the seller concealing the true price. The paper also reviews contemporary applications of Tawliya, including: financing foreign trade through Islamic banks, charitable microfinance for providing goods to the poor in installments, the sale of assets recovered in court liquidations, and zero-interest installment sales to consumers as promotional offers. The paper concluded that while secular laws recognize the concept of trusteeship, they differ fundamentally from Islamic jurisprudence in both source and purpose. Secular laws consider it merely a means of transparency and reducing fraud, whereas Islamic jurisprudence views it as a moral value and a binding trust. The paper recommended the importance of adhering to Sharia principles in contemporary applications, particularly regarding the receipt of goods and full disclosure of costs.